Perancangan Katalog Produk Furniture Berbasis Web sebagai Media Pemasaran SJF Teakwood Jepara - Arie Atwa Magriyanti; Haryo Kusumo; Raditiya Ade Pratama (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
SJF Teakwood is a producer and sales of various kinds of furniture. So far, the promotional media used by SJF Teakwood is through social media Instagram, Facebook and WhatsApp. However, using the promotional media above is considered less specific, so it is necessary to add interesting media to attract the public to the company. This study uses the R&D method. The type of research used is qualitative research. Qualitative research is a research method that uses data in the form of written or spoken words from people and people's behavior observed in a natural context. The results of the validation value from internal experts got a score of 32, external experts 38 and product users got a score of 37 which is included in the very good category, so this web-based furniture product catalog is declared valid for use. So it can be concluded that the Web-Based Furniture Product Catalog as a Marketing Media for SJF Teakwood Jepara is worthy of being used effectively.